Image fusion using hybrid methods in multimodality medical images. - Yadav, Satya Prakash; Yadav, Sachin (Medical & Biological Engineering & Computing, 2020)
An image fusion based on multimodal medical images renders a considerable enhancement in the quality of fused images. An effective image fusion technique produces output images by preserving all the viable and prominent information gathered from the source images without any introduction of flaws or unnecessary distortions. This review paper intends to bring out the process of image fusion, its utilization in the medical domain, merits, and demerits and reviews the perspective of multimodal medical image fusion. It also discusses the involvement of various medical entities like medical resonance imaging (MRI), positron emission tomography (PET), and computed tomography (CT). The usefulness of such modalities is presented, suggesting plausible hybrid modality combinations which could greatly enhance image fusion. This review also discusses innovative dispositions in the medical image fusion techniques for the achievement of incisively desired, quality images focused on fusion with wavelet transform and use of independent component analysis (ICA) and principal component analysis (PCA) techniques for the purpose denoising and data dimension reductions. Additionally, the future-prospects of an ideal technique for medical image fusion through the utilization of various medical modalities have been also discussed in this review paper. Graphical abstract.